OP0234 Clinical and biologic effects of icosl blockade by amg 557 in subjects with lupus arthritis. (15th June 2017) - Cheng, LE; Amoura, Z; Cheah, B; Hiepe, F; Sullivan, BA; Zhou, L; Arnold, GE; Tsuji, WH; Merrill, JT; Chung, JB
Abstract : Background: Blockade of inducible costimulatory ligand (ICOSL) might be a promising approach for autoimmune diseases such as systemic lupus erythematosus (SLE). We evaluated AMG 557, an anti-ICOSL monoclonal antibody, in an exploratory phase 1b study of SLE subjects with inflammatory arthritis, by withdrawing background therapies to improve interpretability of a small study. Objectives: To investigate potential efficacy, safety, and tolerability of AMG 557 in subjects with lupus arthritis. Methods: This double-blind, randomized, placebo-controlled trial enrolled subjects with SLE and active lupus arthritis (≥4 tender and 4 swollen joints) and Systemic Lupus Erythematosus Disease Activity Index [SLEDAI] score ≥6 despite stable background immunosuppressants. Upon enrollment, investigators were permitted to use up to 20 mg/day of prednisone, which was tapered by day 85 to 7.5 mg/day or 50% of baseline, whichever was lower. Subjects received AMG 557 210 mg or placebo once weekly for 3 weeks followed by 10 additional doses every other week until day 155. At day 29, background immunosuppressants were withdrawn. The primary clinical endpoint was a composite Lupus Arthritis Responder Index at day 169; response was defined as achieving: (1) 50% decrease in combined tender and swollen joint counts, and (2) ≥1 letter improvement in the musculoskeletal subsystem of the British Isles Lupus Assessment Group (BILAG) index and (3) prespecified immunosuppressant medication withdrawal and/or prednisone taper. Safety was a co-primary endpoint. Exploratory endpoints included safety, 4-point reduction of SLEDAI, clinical indices (SLEDAI, BILAG), complement components, autoantibodies, and lymphocyte populations. Results: Twenty subjects (19 females) were randomized (10 AMG 557, 10 placebo) at 8 sites in North America, Asia, and Europe. The primary endpoint was met by 3/10 subjects receiving AMG 557 and 1/10 subjects receiving placebo ( P =ns). A 4-point decrease in SLEDAI score was achieved by 7/10 subjects on AMG 557 and 2/10 subjects on placebo. At day 169, subjects receiving AMG 557 had decreases from baseline in mean global BILAG and SLEDAI scores of 36% and 48% respectively, compared to 25% and 11% in subjects receiving placebo. Lupus-associated biomarkers, including serum complement indices (C3, C4, and CH50), and autoantibodies, including anti-dsDNA, demonstrated trends towards improvement relative to placebo. Treatment-emergent adverse events (AEs) were similar between placebo and AMG 557 arms; most commonly headache and upper respiratory tract infection. Conclusions: Results from this exploratory placebo-controlled trial in lupus arthritis suggest potential clinical benefit of ICOSL blockade by AMG 557. These data support further clinical trials intervening in this costimulatory pathway in SLE and other autoimmune diseases. Disclosure of Interest: L. Cheng Shareholder of: Amgen Inc., Employee of: Amgen Inc., Z. Amoura Consultant for: GlaxoSmithKline, AstaZeneca, BristolMyerSquibb, Amgen Inc., B. Cheah Grant/research support from: Merck, F. Hiepe Grant/research support from: Sanofi, Amgen Inc., GlaxoSmithKline, AstaZeneca, Ablynx, Consultant for: Baxalta, AstaZeneca, BristolMyerSquibb, GlaxoSmithKline, Novartix, Miltenyi, Neovacs, Hexal, Neovi, Speakers bureau: Pfizer Inc., Roche, UCB, B. Sullivan Shareholder of: Amgen Inc., Employee of: Amgen Inc., L. Zhou Shareholder of: Amgen Inc., Employee of: Amgen Inc., G. Arnold Shareholder of: Amgen Inc., Employee of: Amgen Inc., W. Tsuji Shareholder of: Amgen Inc., Johnson&Johnson, Consultant for: Celimmune, Seattle Genetics, Resolve Therapeutics, Employee of: Formerly Amgen Inc.; Partner in the Cascadia Drug Development Group, J. Merrill Consultant for: EMD Serono, BristolMyerSquibb, Human Genome Sciences, UCB, AstraZeneca, Celgene, J. Chung Shareholder of: Amgen Inc., Employee of: Amgen Inc.